Ba2+, Mg2+ Doped Sr3Al2O5Cl2:Eu2+ Phosphor for Potential Application in Light-Emitting Diodes - Liu, Bitao; Tian, Liangliang; Peng, Lingling; Han, Tao; Pu, Yong; Cai, Yanhua (Asian Journal of Chemistry, 2014)
The Ba2+ and Mg2+ doped Sr3Al2O5Cl2:Eu2+ synthesized via traditional solid reaction. Photoluminescence spectrum, powder x-ray diffraction and thermal quenching were used to detect these phosphors. The results showed that both of Ba2+ and Mg2+ doped sample showed an enhanced luminescent property. Additionally, due to the difference in the ion radius, the crystal field would alter with changed lattice parameters. The Ba2+ doped sample showed a blue shift from 620 to 610 nm while the Mg2+ doped showed a red-shift from 620 to 630 nm. The thermal quenching also investigated in detail. In general, these phosphors showed potential application in light emitting diodes to obtain warm white light.